Analysis of Particulate matter (PM10) in Malaysia using Markov chain model / Nur Nadzirah Mustafa - Mustafa, Nur Nadzirah; Hasan, Husna (Universiti Teknologi MARA Cawangan Pulau Pinang, 2017)
These Particulates matter (PM10) received great attention due to its potential to cause adverse health effects. This study proposes the application of Markov chain model onto extreme concentration. Data of daily maximum PM10 concentration for fifteen years at ten different locations of the monitoring stations selected at random was observed. Transition probability matrix was determined and Markov chain model was fitted. Chisquare test for independence was conducted. States of transition are dependent of the observatory stations and the state transition chain does follow Markov chain property. The behavior of the transition state shows that Pasir Gudang, Petaling Jaya and Melaka recorded to have the highest value of PM10 concentration while Kota Kinabalu has recorded the healthiest Air Pollutant Index (API) value throughout the past fifteen years. The number of transitions of days for the value of PM10 concentration to be in its steady state for each station is between 36 to 79 days.